2023
DOI: 10.1002/adfm.202300639
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Terahertz Generation: Chiral and Achiral Meta‐Atom Coupling

Abstract: Generation and manipulation of terahertz (THz) waves are of vital importance for advancing THz technology. Nonlinear metasurfaces allow effective integration of both processes into a single compact device. However, such existing THz devices commonly rely on utilizing a single meta‐atom, which has fixed THz generation properties and thus limits the range of achievable functionalities. Here, it is demonstrate how coupling between different meta‐atoms within the unit‐cell can be used as a degree of freedom for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The development of metamaterials has emerged as a breakthrough approach with unique electromagnetic properties, including negative refractive index [2], [3] and perfect lensing [4] capabilities, which are unattainable with conventional materials. This study targets metasurface devices with narrowband resonances for advanced THz modulation [5], [6], [7], stressing the significance of achieving electromagnetically induced transparency-like (EIT-like) resonances [8], [9] with higher quality (Q) factors.…”
Section: Introductionmentioning
confidence: 99%
“…The development of metamaterials has emerged as a breakthrough approach with unique electromagnetic properties, including negative refractive index [2], [3] and perfect lensing [4] capabilities, which are unattainable with conventional materials. This study targets metasurface devices with narrowband resonances for advanced THz modulation [5], [6], [7], stressing the significance of achieving electromagnetically induced transparency-like (EIT-like) resonances [8], [9] with higher quality (Q) factors.…”
Section: Introductionmentioning
confidence: 99%
“…TVBs have potential applications in high-speed THz communication, THz imaging, and atom trapping [ 6 , 7 , 8 , 9 , 10 ], and the generation of a TVB has been an important topic in the past few years [ 11 ]. Recently, by introducing electromagnetically induced transparency coupling to control nonlinear THz generation, a TVB with a different OAM was achieved [ 12 ]. Lu et al reported that a hybrid nonlinear plasmonic metasurface incorporating indium tin oxide can be used to generate a TVB [ 13 ].…”
Section: Introductionmentioning
confidence: 99%